“I know that I can help the person and that is priceless to me”—a qualitative study on tasks and experiences of peers in mental healthcare for refugees - Bogatzki, Lea; Potter, Flurina; Trauner, Luisa; Mier, Daniela; Odenwald, Michael (Frontiers in Public Health, 2025)
BackgroundNumerous barriers prevent refugees from accessing indicated psychotherapy in the German healthcare system. Peer support emerges as a potential key element to overcome utilization barriers for refugees in the future. Since 2017, the pilot project “Coordinated Psychotherapeutic Treatment with the Involvement of Peer Support Workers” (COPEER) has been developed and implemented and is currently being evaluated. In COPEER, supervised, but autonomously acting peer support workers (PSWs) accompany and support refugees with mental disorders in the healthcare system.ObjectiveThis study focuses on the qualitative description of the PSWs' work reality and their positive and negative work-related experiences in COPEER to assess the feasibility and relevance of their role.MethodAn exploratory and qualitative approach with purposive sampling was chosen; face-to-face expert interviews were conducted using a semi-structured guide with 8 PSWs (3 women, 5 men; age M = 43 years). The evaluation was carried out using Mayering's Qualitative Content Analysis.ResultsFive main task areas within the work reality of PSWs could be identified: organization, physical accompaniment, cultural mediation, motivation and emotional support. PSWs reported both positive and negative work-related experiences, with positive aspects being mentioned more frequently, such as high meaningfulness and a personal learning process. Negative experiences were often encountered during the initial phase of their work, e.g., problems managing the professional relationship. The mandatory continuous supervision provided by COPEER was described as helpful.ConclusionPSWs take on important tasks that actively help to overcome central barriers to the regular health care system for refugees. In doing so, they experience both negative and positive aspects. Training and regular supervision appear to be crucial to successfully cope with work-related demands. In sum, the results show that a peer approach, as implemented in COPEER, can help to overcome barriers and enable equal access to mental health care for a particularly disadvantaged patient group.